2014
DOI: 10.1371/journal.pone.0101558
|View full text |Cite
|
Sign up to set email alerts
|

Toll like Receptor 3 & 4 Responses of Human Turbinate Derived Mesenchymal Stem Cells: Stimulation by Double Stranded RNA and Lipopolysaccharide

Abstract: Background and objectivesMultipotent mesenchymal stromal cells (MSCs) represent a promising cell-based therapy for a number of inflammatory or autoimmune diseases. Herein, Toll like receptor (TLR) expression by MSCs and their immune regulatory roles are investigated. In this study, we investigated the influence of TLR on the immune response, proliferation, and differentiation potential of human turbinated MSC (hTMSC) cultures in vitro.Subjects and MethodsAfter isolating hTMSCs from discarded inferior turbinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 20 publications
12
29
0
Order By: Relevance
“…Similar pro-proliferative effects have been observed after stimulation of adult human bone marrow MSCs with 1 μg/ml LPS from E. coli (O55:B5) for 48 h [72]. Besides bone marrow MSCs, LPS may also have proliferation inducing effect in peripheral MSCs isolated from human turbinate tissue [18]. Remarkably, exposure of this MSC-population to 10 ng/ml LPS (1 h) has only weak pro-proliferative effect which could only be observed 48 h after the treatment.…”
Section: Proliferationsupporting
confidence: 67%
See 2 more Smart Citations
“…Similar pro-proliferative effects have been observed after stimulation of adult human bone marrow MSCs with 1 μg/ml LPS from E. coli (O55:B5) for 48 h [72]. Besides bone marrow MSCs, LPS may also have proliferation inducing effect in peripheral MSCs isolated from human turbinate tissue [18]. Remarkably, exposure of this MSC-population to 10 ng/ml LPS (1 h) has only weak pro-proliferative effect which could only be observed 48 h after the treatment.…”
Section: Proliferationsupporting
confidence: 67%
“…Similarly, LPS treatment of human adipose tissuederived MSCs seems to increase their osteogenic potential [74]. In contrast to these studies, short-term exposure (1 h) to LPS had no significant effects on osteogenic and adipogenic differentiation of human turbinate-derived MSCs [18]. Notably, in mice lacking TLR4, neither osteogenic nor adipogenic differentiation were significantly changed compared to MSCs from control animals [76].…”
Section: Differentiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Explanation of these different outcomes may be based on the findings that TLR3 and TLR4 activate MSCs in different ways. Activation through TLR4 with LPS induced the pro-inflammatory phenotype of MSCs where secretion of IL-6, IL-8, and TGF-β was intensified by co-stimulation with IFN-γ 7779. On the other hand, activation through TLR3 with polyinosinic:polycytidylic acid (poly I:C) induced anti-inflammatory phenotype of MSCs where production of IDO, PGE-2, IL-4, and IL-1RA was detected 77,79.…”
Section: Activation Of Immunomodulatory Capacity Of Mscsmentioning
confidence: 99%
“…Thus, influencing MSCs phenotype and modulating MSCs responses remain an important task in research related to tissue repair. Various studies have shown that activation of Toll-like receptors (TLR) pathway, scavenger receptor pathway or growth factor pathway can influence the capacity of these cells to differentiate into bone, fat or cartilage by increasing or decreasing their capacity [44][45][46][47]. Therefore understanding how different agonists of these pathways may influence the MSCs responses could help to identify new molecules with a beneficial impact on MSCs, which can be used in the repair of tissues.…”
Section: Introductionmentioning
confidence: 99%